Rethinking the path from evidence to decision-making - Alon Rasooly; Eliana Ben-Sheleg; Nadav Davidovitch; Moriah Ellen (BMC, 2023)
Abstract Evidence-informed decision-making is increasingly recognized as a standard for policymaking in many fields, including public health. However, many challenges exist in identifying the appropriate evidence, disseminating it to different stakeholders, and implementing it in various settings. The Israel Implementation Science and Policy Engagement Centre (IS-PEC) was established at Ben-Gurion University of the Negev to "bridge the gap" between scientific research and policy. As an illustrative case study, IS-PEC is conducting a scoping review on strategies to engage senior citizens in Israel when developing health policy. In May 2022, IS-PEC brought together international experts and Israeli stakeholders to increase knowledge in the field of evidence-informed policy, develop a research agenda, strengthen international collaborations, and create a community for sharing experience, research, and best practices. Panelists presented the importance of communicating clear, accurate bottom-line messages with the media. Also, they highlighted the once-in-a-generation opportunity to promote the uptake of evidence in public health due to the increased public interest in evidence-informed policymaking post-COVID-19 pandemic and the need to build systems and centers to support the systematic use of evidence. Group discussions focused on various aspects of communication, including challenges and strategies when communicating to policymakers, understanding the nuances of communication between scientists, journalists, and the public, and some ethical issues surrounding data visualization and infographics. Panelists participated in a passionate debate regarding whether and how values play a role when conducting, analyzing, and communicating evidence. Takeaway lessons from the workshop included that going forward, Israel must create lasting systems and a sustainable environment for evidence-informed policy. Novel and interdisciplinary academic programs must be developed to train future policymakers in various fields, including public health, public policy, ethics, communication, social marketing, and infographics. Sustainable professional relationships between journalists, scientists, and policymakers must be fostered and strengthened based on mutual respect and a shared commitment to creating, synthesizing, implementing, and communicating high-quality evidence to serve the public and individual wellbeing.